Modernisasi Aspek Relasional Pemerintah Daerah: Menengok Sejarah, Menatap Masa Depan - Samodra Wibawa (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2000)
The history of Nusantara was since 1600s broken down by the Europeans, so that it has developed not in a "natural" way, in which the governmental style in the independence Indonesia was always in the tendency to centralism, and this has demolished the individual and also local governmental creativities. To make Indonesia back to its "own" socio-political development, the author argues that the decentralisation policies were not satisfied enough and suggests four perspectives on the relation between Kabupaten-Province-State in the 21" century: firstly, the relationship between them should be based on the subsidiary principal, not hierarchical but co-operative, coordinative and many-sided; secondly, the election system should be districtly and the election of the governmental chefs directly; thirdly, the capital city of every governmental level should be moved each 15-20 years; and fourthly, every political actor should be educated so that s/he is od,ready to compromise and the bureaucracy (includes the army) should be professional and clean.